Accuracy of maximal expiratory flow-volume curve curvilinearity and fractional exhaled nitric oxide for detection of children with atopic asthma - Sang Hoo Park; Min Ji Im; Sang-Yong Eom; Youn-Soo Hahn (Korean Pediatric Society, 2017)
PurposeAirway pathology in children with atopic asthma can be reflected by the concave shape of the maximal expiratory flow-volume (MEFV) curve and high fractional exhaled nitric oxide (FeNO) values. We evaluated the capacity of the curvilinearity of the MEFV curve, FeNO, and their combination to distinguish subjects with atopic asthma from healthy individuals.MethodsFeNO and angle β, which characterizes the general configuration of the MEFV curve, were determined in 119 steroid-naïve individuals with atopic asthma aged 8 to 16 years, and in 92 age-matched healthy controls. Receiver operating characteristic (ROC) curve analyses were performed to determine the cutoff points of FeNO and angle β that provided the best combination of sensitivity and specificity for asthma detection.ResultsAsthmatic patients had a significantly smaller angle β and higher FeNO compared with healthy controls (both, P<0.001). For asthma detection, the best cutoff values of angle β and FeNO were observed at 189.3° and 22 parts per billion, respectively. The area under the ROC curve for the combination of angle β and FeNO improved to 0.91 (95% confidence interval [CI], 0.87-0.95) from 0.80 (95% CI, 0.75-0.86; P<0.001) for angle β alone and 0.86 (95% CI, 0.82-0.91; P=0.002) for FeNO alone. In addition, the combination enhanced sensitivity with no significant decrease in specificity.ConclusionThese data suggest that the combined use of the curvilinearity of the MEFV curve and FeNO is a useful tool to differentiate between children with and without atopic asthma.